THE ACCOUNTANT PROFESSIONAL AS A CURRENT USER OF PROFESSIONAL JUDGMENT - Viorica Mirela ŞTEFAN-DUICU (Challenges of the Knowledge Society, 2015)
Professional judgment governs the evolution of a process in the absence of any relevant procedural regulations. In this paper we will describe both the building components of the professional judgment and the accounting professional as a practitioner whom use most often the expression of the above mentioned type of judgment.